A qualitative research on health education needs of pregnant women with gestational diabetes mellitus (妊娠期糖尿病孕产妇健康教育需求的质性研究) - TAN Minjing (覃敏静); YANG Miaomiao (杨苗苗); WANG Kaihua (王凯华); LUO Chunmiao (罗春苗); ZHOU Jinchang (周金嫦) (中西医结合护理)
Objective To understand the health education needs of pregnant women with gestational diabetes mellitus, and provide references for the development of targeted nursing measures. Methods From October to December 2020, the purposive sampling was adopted to select 12 pregnant women with diabetes mellitus who gave birth in our hospital as the research objects. The phenomenological research method in the qualitative research was used to conduct semi-structured interviews. The Colaizzi's 7-step analysis method was used to analyze the data. Results Five themes were extracted: psychosocial support throughout the whole process, health education needs for diet and exercise treatment options, related discomforts and health education needs for coping, health education needs for home self-care, and diversified ways to obtain health education information. Conclusion The health education need of pregnant women with gestational diabetes mellitus has its own particularity . Medical staff should pay attention to their needs and provide targeted services for health education needs. (目的 深入了解妊娠期糖尿病孕产妇健康教育需求, 为制定针对性的护理措施提供参考。方法 2020年10月—12月, 采用目的抽样法选取在医院就诊和住院分娩的妊娠期糖尿病孕产妇12例为研究对象, 采用质性研究中的现象学研究方法进行半结构式访谈, 运用Colaizzi 7步分析法对资料进行整理分析和提炼主题。结果 分析提炼出5个主题, 即心理社会支持贯穿全程、饮食运动治疗方案选择的健康教育需求、相关不适及应对的健康教育需求、居家自我照护的健康教育需求、获取健康教育信息途径的多样化。结论 妊娠期糖尿病孕产妇健康教育需求有其特殊性, 医护人员应当重视其需求, 有针对性提供健康教育需求服务。)